Solder joint fatigue in a surface mount assembly subjected to mechanical loading - Mohd. Nasir Tamin, author; Yek, Ban Liew, author; Amir N. R. Wagiman, author; Wei, Keat Loh, author; IEEE Transactions on Components and Packaging Technologies (2007) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL